Dampak Isi dan Keakuratan Seleksi Pemasaran Digital terhadap Penjualan Makanan Olahan Ikan Lombok Timur - Sulkiah Sulkiah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Recent empirical studies show that the use of digital marketing among fishermen is still not optimal due to limitations in content creation and limited online media options. Digital marketing has been heralded as an effort to increase sales to fishermen. Unattractive content and target market errors in online media are one of the causes of the failure of fishing businesses to increase sales. Therefore, this research was conducted to determine the effect of digital marketing content and the accuracy of choices on the sales of East Lombok fishermen's processed food. This study analyzes the impact of digital marketing content and the accuracy of selection on sales of processed fishery products. The sample is based on the type of business and business category. Data collection was carried out by distributing questionnaires to 171 fishermen, who sold their products directly to online media using a door to door approach and filling assistance. Data were tested statistically with descriptive analysis, validity and reliability, and linear regression. The results of the study show that the content and accuracy of digital marketing choices have a positive effect on sales of processed fisherman products. These results show the importance of content choices and digital marketing to increase sales of processed fishery products in East Lombok. Fishermen can increase their ability and willingness to explore content and methods for selecting online media to promote their products in order to maximize sales results. Data were tested statistically with descriptive analysis, validity and reliability, and linear regression. The results of the study show that the content and accuracy of digital marketing choices have a positive effect on sales of processed fisherman products. These results show the importance of content choices and digital marketing to increase sales of processed fishery products in East Lombok. Fishermen can increase their ability and willingness to explore content and methods for selecting online media to promote their products in order to maximize sales results. Data were tested statistically with descriptive analysis, validity and reliability, and linear regression. The results of the study show that the content and accuracy of digital marketing choices have a positive effect on sales of processed fisherman products. These results show the importance of content choices and digital marketing to increase sales of processed fishery products in East Lombok. Fishermen can increase their ability and willingness to explore content and methods for selecting online media to promote their products in order to maximize sales results. that the content and accuracy of digital marketing choices have a positive effect on sales of processed fisherman products. These results show the importance of content choices and digital marketing to increase sales of processed fishery products in East Lombok. Fishermen can increase their ability and willingness to explore content and methods for selecting online media to promote their products in order to maximize sales results. that the content and accuracy of digital marketing choices have a positive effect on sales of processed fisherman products. These results show the importance of content choices and digital marketing to increase sales of processed fishery products in East Lombok. Fishermen can increase their ability and willingness to explore content and methods for selecting online media to promote their products in order to maximize sales results.